Project management : case studies - Kerzner, Harold (John Wiley & Sons, Inc., 2013)
Providing a comprehensive collection of case studies in one accessible volume, Project Management Case Studies features one hundred cases drawn from real companies that illustrate both successful and poor implementation of project management. Covering broad areas of project management plus construction and international project management, this fourth edition of the most popular book of project management case studies maintains the popular ""super case"" on the Iridium Project. Project Management Case Studies supplements any textbook on the subject.
Includes index.
Keywords: Project management -- Case studies.; elektronické knihy; electronic books